Pancasila sebagai Living Ideology: Strategi Deradikalisasi dan Penguatan Toleransi di Tengah Arus Globalisasi Digital - Muhammad Haizul Falah; Matroni Matroni (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study explores the strategic role of Pancasila as a living ideology in addressing the rising challenges of radicalism and intolerance in the era of digital globalization. The increasing spread of radical ideologies through social media, along with the growing exclusivist attitudes within Indonesia’s multicultural society, demands an adaptive and applicable ideological approach. This research employs a descriptive qualitative method using literature review techniques. The findings indicate that collaboration among state institutions, civil society organizations, and educational institutions is crucial in grounding the values of Pancasila within public and digital spaces. Deradicalization strategies that emphasize ideological education, media literacy, and humanistic approaches have proven more effective in fostering tolerance and preventing the spread of extremist ideologies. This study affirms that Pancasila must continuously be revitalized through cross-sectoral, concrete actions to remain relevant and influential in preserving national unity.